Republic of Paraguay Institutional and Governance Review Breaking with Tradition : Overcoming Institutional Impediments to Improve Public Sector Performance - World Bank (Washington, DC, 2012)
The present study uses examples from all three branches of Government - the Ministry of Finance, the ordinary courts, and the Congress in its budgetary role - to examine the institutional obstacles to their improved performance and the opportunities for targeted changes. It builds on recent analytic work done by Paraguayan academics and others, highlighting the historical and persisting impact of the traditional political practices. The arguments emphasize that the particularistic use of public resources has been and remains key to obtaining and holding political power in Paraguay. The study's goals were eminently practical to provide Paraguay's reformers with insights as to how they can escape a series of vicious circles. As they understand the basics quite well, the emphasis here was on their more detailed application at the organizational and sub-organizational levels.